2017
DOI: 10.1186/s40413-017-0157-0
|View full text |Cite
|
Sign up to set email alerts
|

Allergic profiles of mothers and fathers in the Japan Environment and Children’s Study (JECS): a nationwide birth cohort study

Abstract: BackgroundThe Japan Environment and Children’s Study (JECS) is a nationwide, multicenter, prospective birth cohort investigation launched by the Ministry of Environment in Japan. The purpose of the JECS is to evaluate the influence of prenatal and postnatal exposures to environmental factors on the postnatal health of the children. In this study, we evaluated the allergic characteristics of parents within the JECS cohort.MethodsThis study covered a wide geographical area and encompassed 15 regional centers. We… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 42 publications
(27 citation statements)
references
References 21 publications
0
27
0
Order By: Relevance
“…The results of the ImmunoCAP system were given as exact values in UA/mL. Values of 0.35 UA/mL or higher were taken as a sign of sensitization (Yamamoto-Hanada et al, 2017 ).…”
Section: Methodsmentioning
confidence: 99%
“…The results of the ImmunoCAP system were given as exact values in UA/mL. Values of 0.35 UA/mL or higher were taken as a sign of sensitization (Yamamoto-Hanada et al, 2017 ).…”
Section: Methodsmentioning
confidence: 99%
“…A systematic review demonstrated that the pooled lifetime and point prevalence of self-reported FA was 17.3% (95% CI 17.0–17.6) in Europe [ 36 ]. From a large-scale birth cohort study (JECS Study), the prevalences of asthma, allergic rhinitis (hay fever), atopic dermatitis, and food allergy were 10.9, 36.0, 15.7 and 4.8%, respectively, among 99,013 mothers in Japan [ 37 ]. In addition, 73.9% mothers had positive IgE sensitization.…”
Section: Discussionmentioning
confidence: 99%
“…Although it is not a clinical trial, the Japan Environment and Children’s Study (JECS) is registered with the University Hospital Medical Information Network Clinical Trials Registry, number UMIN000030786. The JECS is a nationwide, multicentre, prospective birth cohort study conducted by the Ministry of Environment of Japan, and its protocol and major hypotheses have been published as a protocol paper [ 12 – 15 ]. A total of 103,099 pregnant women were recruited from the general population of Japan for the JECS at 15 research centres covering a wide geographical area of Japan, from the north of the country (Hokkaido) to the south (Okinawa), from April 2011 to March 2014.…”
Section: Methodsmentioning
confidence: 99%
“…The prevalence of asthma and eczema among Japanese children is 13.3% and 24.5%, respectively [ 11 ]. According to a nationwide birth cohort study, about 36% of pregnant women in Japan have a history of pollinosis and 55.6% are IgE-sensitised to Japanese cedar [ 12 ]. Given the relatively high prevalence of allergies in Japan, it is important to investigate potential triggers and preventions for the development of this condition.…”
Section: Introductionmentioning
confidence: 99%